2019
DOI: 10.1097/pas.0000000000001207
|View full text |Cite
|
Sign up to set email alerts
|

PRDM10-rearranged Soft Tissue Tumor

Abstract: Gene fusion transcripts containing PRDM10 were recently identified in low-grade undifferentiated pleomorphic sarcomas (UPS). Here, we describe the morphologic and clinical features of 9 such tumors from 5 men and 4 women (age: 20 to 61 y). Three cases had previously been diagnosed as UPS, 3 as superficial CD34-positive fibroblastic tumor (SCD34FT), 2 as pleomorphic liposarcoma, and 1 as pleomorphic hyalinizing angiectatic tumor. The tumors were located in the superficial and deep soft tissues of the thigh/knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…9 Their findings suggest that superficial CD34 positive fibroblastic tumor is genetically heterogenous and further investigation of this entity is warranted. 9 A low-grade myxofibrosarcoma was excluded in the current tumor based on the age of the patient, the lack of characteristic curvilinear vasculature, and the wellcircumscribed nature of the lesion with strong diffuse CD34 positivity and focal keratin staining. MIFS occurs at acral sites, displays myxoid nodules and pseuodolipoblasts and is typically CD34 negative.…”
Section: Discussionmentioning
confidence: 99%
“…9 Their findings suggest that superficial CD34 positive fibroblastic tumor is genetically heterogenous and further investigation of this entity is warranted. 9 A low-grade myxofibrosarcoma was excluded in the current tumor based on the age of the patient, the lack of characteristic curvilinear vasculature, and the wellcircumscribed nature of the lesion with strong diffuse CD34 positivity and focal keratin staining. MIFS occurs at acral sites, displays myxoid nodules and pseuodolipoblasts and is typically CD34 negative.…”
Section: Discussionmentioning
confidence: 99%
“…PRDM10 gene fusions with either MED12 or CITED2 have been reported in a small proportion of undifferentiated pleomorphic sarcomas. These tumors have a relatively benign course, a distinct expression pattern and no or limited other mutations or numerical chromosomal aberrations ( 55 , 56 ). PRDM10 increases B-cell lymphoma-2 (Bcl-2) expression in vitro ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using RNA-seq and other methodologies, analysis of 84 soft tissue sarcomas revealed that a significant subset of low-grade undifferentiated pleomorphic sarcoma (UPS) showed a gene fusion of PRDM10 either with MED12 or CITED2, suggesting that these rearrangements were specific for this less aggressive UPS subset [161]. Moreover, PRDM10-rearranged soft tissue tumors are characterized by pleomorphism and a low mitotic count [162]. Currently studies using integrated bioinformatics and network analysis have also recognized the role of PRDM10 in the onset, progression, and drug resistance of many malignancies, such as hepatocellular, prostate, and nasopharyngeal carcinoma, as well as gastric and rectum cancers [163][164][165][166][167][168]; although in our previous TGCA analysis, PRDM10 was either mutated or overexpressed in certain cancer types [45].…”
Section: Prdm10mentioning
confidence: 99%